Associação entre polimorfismos no gene da glicoproteína-P (PgP) e resistência múltipla a anti-helmínticos em Haemonchus contortus e identificação de fatores de risco relacionados - Mello, Suelen Scarpa de (Universidade Federal de São Carlos, 2014)
Among the sheep parasites, Haemonchus contortus is the most prevalent and pathogenic nematode in tropical areas, causing huge economic losses. Alterations in the gene encoding the membrane P-glycoprotein (PgP) have been associated with multidrug resistance. The goal of this study was to identify single nucleotide polymorphisms (SNPs) on the PgP gene in H. contortus by comparing two isolates with different status of anthelmintic resistance. For this purpose, two ewes were experimentally infected, one with a susceptible H. contortus isolate (McMaster, Australia) and the other with a multidrug-resistant isolate (Embrapa2010, Brazil). Feces from infected animals were submitted to coproculture in order to obtain larvae and, after the slaughter of the ewes, adults H. contortus were collected from abomasum and individually submitted to DNA extraction. For the evaluation of potential molecular markers of geographic isolation, larvae originating from coprocultures of two other Brazilian isolates (Bahia and Pernambuco), with no determined resistance status, were also submitted to DNA extraction. After PCR amplification of DNA extracted from adults H. contortus, a fragment of the PgP gene was sequenced and six SNPs (position described in relation to the sequence of contig 004690 from the Wellcome Trust Sanger Institute) were identified : 508 (A> G in exon), 580 (G> A), 601 (G> C), 800 (G> A), 845 (G> T), and 878 (G> T), the last five in introns. The Fisher's exact test, applying the Bonferroni correction, revealed a significant association (P<0.01) between 508, 580, 601, 845 and 878 SNPs and the state of resistance to anthelmintics. Among these SNPs, 601 and 878 are in linkage disequilibrium and form the CC haplotype associated (P < 0.05) to resistance and the GG haplotype associated to susceptibility. Considering that there is considerable genetic differentiation between different continental areas in H. contortus, the frequencies of the SNPs were compared between the Brazilian isolates and the susceptible Australian one. It was found that the SNPs 580 and 845 may be associated with geographic isolation. We conclude that the 508, 601 and 878 SNPs in the P-glycoprotein gene can be molecular markers for multiple resistance to anthelmintics, and that the 580 and 845 SNPs can be candidate markers of geographical isolation in H. contortus. We developed software for Risk Analysis Development of Parasitic Resistance to Anthelmintics in Sheep (SARA) which will provide information that may guide the rational use of anthelmintics.

Among the sheep parasites, Haemonchus contortus is the most prevalent and pathogenic nematode in tropical areas, causing huge economic losses. Alterations in the gene encoding the membrane P-glycoprotein (PgP) have been associated with multidrug resistance. The goal of this study was to identify single nucleotide polymorphisms (SNPs) on the PgP gene in H. contortus by comparing two isolates with different status of anthelmintic resistance. For this purpose, two ewes were experimentally infected, one with a susceptible H. contortus isolate (McMaster, Australia) and the other with a multidrug-resistant isolate (Embrapa2010, Brazil). Feces from infected animals were submitted to coproculture in order to obtain larvae and, after the slaughter of the ewes, adults H. contortus were collected from abomasum and individually submitted to DNA extraction. For the evaluation of potential molecular markers of geographic isolation, larvae originating from coprocultures of two other Brazilian isolates (Bahia and Pernambuco), with no determined resistance status, were also submitted to DNA extraction. After PCR amplification of DNA extracted from adults H. contortus, a fragment of the PgP gene was sequenced and six SNPs (position described in relation to the sequence of contig 004690 from the Wellcome Trust Sanger Institute) were identified : 508 (A> G in exon), 580 (G> A), 601 (G> C), 800 (G> A), 845 (G> T), and 878 (G> T), the last five in introns. The Fisher's exact test, applying the Bonferroni correction, revealed a significant association (P<0.01) between 508, 580, 601, 845 and 878 SNPs and the state of resistance to anthelmintics. Among these SNPs, 601 and 878 are in linkage disequilibrium and form the CC haplotype associated (P < 0.05) to resistance and the GG haplotype associated to susceptibility. Considering that there is considerable genetic differentiation between different continental areas in H. contortus, the frequencies of the SNPs were compared between the Brazilian isolates and the susceptible Australian one. It was found that the SNPs 580 and 845 may be associated with geographic isolation. We conclude that the 508, 601 and 878 SNPs in the P-glycoprotein gene can be molecular markers for multiple resistance to anthelmintics, and that the 580 and 845 SNPs can be candidate markers of geographical isolation in H. contortus. We developed software for Risk Analysis Development of Parasitic Resistance to Anthelmintics in Sheep (SARA) which will provide information that may guide the rational use of anthelmintics.
Keywords: Genética e evolução; Marcador molecular; Helminto; Haemonchus contortus; Glicoproteína-p; Resistência múltipla a antihelmínticos; P-glycoprotein; Multidrug resistance to anthelmintics; Molecular marker; CIENCIAS BIOLOGICAS::GENETICA